Keefektifan Media Power Point Dalam Keterampilan Menulis Hanzi 汉字 Siswa Kelas VIII SMP Frater Makassar - Baso Heriadi; Misnawaty Usman; Muh Anwar (Universitas Negeri Makassar, 2022)
Baso Heriadi, 2021. “The Effectiveness of Power Point Media in Writing Skills Hanzi, a Class VIII Student of the Frater Makassar Junior High School”. Essay. Mandarin Education Study Program. Department of Foreign Language Education. Faculty of Languagesand Letters. Makassar State University (supervised by Muh. Anwar and Misnawaty Usman). This research is an quasi experimental , which has 2 variables, namely power point media as the independent variable, namely writing hanzi as the dependent variable. The population of this study was 209 class VIII students at Frater Makassar Junior High School, the sample used by random sampling in this study was class VIII A students at Frater Makassar Junior High School, which amounted to 20 students as control class and class VIII B Middle School students. First Frater Makassar, which consisted of 20 students as the experimental class. The data of this study were obtained through the Chinese writing test and analyzed using the T test. H1: The use of power point media was effective in Chinese writing skills Grade VIII students of the Frater Makassar Junior High School, were accepted. H0 : The use of power point media is not effective in Chinese writing skills Grade VIII students of the Frater Makassar Junior High School, are rejected. The results of this study indicate that tcount is greater than ttable (13.47> 2.03) with a significant level of 0.05. This means that the use of power point slides is effective for writing Chinese students in class VIII of the Frater Makassar Junior High School.Keywords: Effectiveness, Power Point Media, Writing Skill, And Hanzi.